Profile of the impact on the oral health of persons with Parkinson's disease during the COVID-19 isolation - Hellen Kevillyn Brito de SOUZA; Jonatas Silva de OLIVEIRA; Crislayne Felix da SILVA; Maria das Graças Wanderley de Sales CORIOLANO; Carla Cabral dos Santos Accioly LINS (Universidade Estadual Paulista, 2023)
Abstract Introduction the Covid-19 pandemic impacted elderly persons with Parkinson's Disease (PD), influencing their daily activities and quality of life. Objective to evaluate the impact on the oral health in people with Parkinson's Disease during the Covid-19 isolation. Material and method the present analytical, quantitative, cross-sectional study uses secondary data sources from 115 health records used in a study carried out from August to December in 2020 through telemonitoring. Sociodemographic aspects and self-perception of quality of life were evaluated using the Oral Health Impact Profile (OHIP-14) questionnaire. The variables studied in the association were: sex, age, duration of PD, civil status, Covid-19 diagnosis and the use of dental prostheses. The software Statistica 13.2 and the Chi-square (X2) test with a significance level of p<0.05 were used. Result after analyzing the database, the final sample consisted of 64 health records that responded to the OHIP-14. 61% were male, with a mean age of 66.6 years, 64% were using dental prostheses, and 74% indicated on the OHIP-14 that they had good oral health self-perception. No significant associations were found among the variables: Age, Sex, Civil Status, Covid diagnosis, Duration of illness, Use of dental prostheses and the OHIP-14 (p>0.05). Conclusion it was found that people with Parkinson's Disease showed a good quality of life, as evaluated using the OHIP-14, and that the Covid-19 isolation did not impact negatively on the oral health.